Regulatory T‐cell stability and functional plasticity in health and disease. Issue 2 (26th December 2022) - Malviya, Vanshika; Yshii, Lidia; Junius, Steffie; Garg, Abhishek D; Humblet‐Baron, Stephanie; Schlenner, Susan M
Abstract: FOXP3‐expressing regulatory T cells (Treg ) are indispensable for immune homeostasis and tolerance, and in addition tissue‐resident Treg have been found to perform noncanonical, tissue‐specific functions. For optimal tolerogenic function during inflammatory disease, Treg are equipped with mechanisms that assure lineage stability. Treg lineage stability is closely linked to the installation and maintenance of a lineage‐specific epigenetic landscape, specifically a Treg ‐specific DNA demethylation pattern. At the same time, for local and directed immune regulation Treg must possess a level of functional plasticity that requires them to partially acquire T helper cell (TH ) transcriptional programs—then referred to as TH ‐like Treg . Unleashing TH programs in Treg, however, is not without risk and may threaten the epigenetic stability of Treg with consequently pathogenic ex‐Treg contributing to (auto‐) inflammatory conditions. Here, we review how the Treg ‐stabilizing epigenetic landscape is installed and maintained, and further discuss the development, necessity and lineage instability risks of TH 1‐, TH 2‐, TH 17‐like Treg and follicular Treg . Abstract : In this article, we discuss mechanisms that install and maintain the Treg ‐stabilizing epigenetic landscape. We further review functional plasticity of Treg into T helper (TH )‐like Treg and how the development of pathogenic ex‐TH ‐like Treg can contribute to inflammatory diseases.